OSR1 and SIX2 drive divergent transcriptional programs in human kidney cells: implications for regeneration and tumorigenesis - Pode-Shakked, Naomi; Cohen-Zontag, Osnat; Omer, Dorit; Harari-Steinberg, Orit; Vax, Einav; Pleniceanu, Oren; Dekel, Benjamin (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundThe nephron progenitor cells generate approximately one million nephrons during human nephrogenesis. At 34-36 weeks of human genstation, silencing of the key kidney progenitor genes results in depletion of this progenitor pool, limiting the regeneration capacity of the mature kidney. Concurrently, the increasing incidence of end-stage kidney disease underscores the urgent need for innovative regenerative strategies.MethodsWe employed lentiviral vectors to ectopically induce two key kidney progenitor genes OSR1 and SIX2 individually or together in primary human adult kidney (hAK) cells. We then analyzed the cellular and molecular consequences through morphological assessments, functional assays, in vivo transplantation studies, and comprehensive transcriptional profiling.ResultsOSR1 and SIX2 induced distinct reprogramming processes with differential functional outcomes; SIX2 overexpression was found to maintain epithelial morphology while significantly enhancing proliferation and clonogenic efficiency. Transcriptionally, SIX2 established epithelialization and cell-cycle networks by downregulating proximal tubule markers while upregulating distal nephron markers and proliferation genes. In vivo, SIX2-expressing cells formed organized tubular structures with a distinct luminal architecture in a proof-of-concept model. In contrast, OSR1 overexpression was found to induce morphological changes and activate developmental morphogenetic pathways, including epithelial tube morphogenesis and canonical Wnt signaling; however, it did not enhance proliferation and showed minimal tubulogenic capacity in vivo. Unexpectedly, OSR1 overexpression led to malignant transformation in one clone and exhibited Wilms’-tumor-like features, including expression of kidney developmental markers (i.e., SIX2, NCAM1, and WT1) and blastemal phenotype.ConclusionOur findings suggest that SIX2 overexpression in primary hAK cells functionally confers enhanced self-renewal and tubulogenic capacity while transcriptionally inducing a proximal-to-distal tubular cell diversion with maintained proliferative programs. In contrast, OSR1 activates the broader developmental morphogenetic networks but poses potential oncogenic risks. The malignant transformation observed with OSR1 overexpression provides insights into the potential cellular origins of Wilms’ tumor and raises important safety considerations for regenerative medicine approaches involving developmental gene induction in adult kidney cells.